The Effect Utilization of Application-Based Learning Resources on Learning Outcomes of Basic Music Theory Subject - Saepulloh, Saepulloh; Rusijono, Rusijono; Mariono, Andi (International Journal for Educational and Vocational Studies, 2020)
This study aims to improve student learning outcomes through the use of application-based learning resources in the NCO Vocational School of Music, Education and Training Center. This study uses Quasy Experimental Design in the experimental class and the control class. Consists of two stages, namely (1) the preparation phase aims to utilize application-based learning resources, (2) the implementation phase uses pre-test and post-test designs in the experimental class and the control class. The results showed that there were differences in the experimental class and the control class through the results of different tests (Mann Whitney) on pre-test and post-test. The pre-test results showed U > Ucritical, conclusions H0 accepted the results of the pre-test there was no difference. Post-test results: U < Severe, conclusions H0 rejected post-test results there are differences. The results of data analysis show that there is an influence of the use of application-based learning resources on Music Theory Basic subjects on experimental class learning outcomes.